Answer:
6x² + x - 12 = (2x + 3) (3x - 4)
Step-by-step explanation:
Factor 6x² + x - 12 by grouping
we need to rewrite the middle term as a sum of two terms whose product is (6* −12) = −72 and whose sum is 1
The middle term = x = 9x - 8x
6x² + x - 12
= 6x² + 9x - 8x - 12 Grouping the first two terms and the last two terms
= (6x² + 9x) + ( - 8x - 12)
From the first two terms take 3x as a common and from the two terms take (-4) as a common
= 3x ( 2x + 3) -4 (2x + 3)
Take (2x + 3) as a common
= <u> (2x + 3) (3x - 4)</u>
The missing proof is the third statement
¹²³⁴⁵⁶⁷⁸⁹⁰⁹⁸⁷⁶⁵⁴³²¹
₁¹₁¹₁
Answer:
The decimal form of the equation is y = 2.5x + 10
The equivalent fraction form is y = (5/2)x + 10 because 5/2 = 2.5
===========================================================
Explanation:
We can pick any two columns from the table to form the two points needed.
I'll pick the first two columns
(1, 12.5)
(2, 15)
Then apply the slope formula to those points
m = (y2-y1)/(x2-x1)
m = (15-12.5)/(2-1)
m = (2.5)/(1)
m = 2.5
Now use that slope with either point mentioned to find the y intercept b.
y = mx+b
12.5 = 2.5*1 + b
12.5 = 2.5 + b
12.5 - 2.5 = b
10 = b
b = 10
Or
y = mx+b
15 = 2.5*2+b
15 = 5+b
15-5 = b
10 = b
b = 10
We end up with the same b value.
We found that m = 2.5 is the slope and b = 10 is the y intercept
Therefore we go from y = mx+b to y = 2.5x + 10
This is the same as saying y = (5/2)x + 10 since 2.5 = 5/2
Answer:
2^1* 3^7
Step-by-step explanation:
8^-1 * 3^3/ 2^-4 * 9^-2
Negative exponents move from the numerator to the denominator or from the denominator to the numerator
2^4*9^2* 3^3 /8^1
Rewriting 9^2 as 3^2^2 = 3^4 and 8 = 2^3
2^4 * 3^3 * 3^4 / 2^3
2^4/ 2^3 = 2 and 3^3 * 3^4 = 3^(3+4) = 3^7
2* 3^7
Answer:
1017.36
Step-by-step explanation: The formula for cone volume is 3.14(r^2)(h/3). Plug in all of your values to get the answer.